2017
DOI: 10.3892/ol.2017.5694
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 knockdown inhibits the growth and invasion of nasopharyngeal cancer stem cells

Abstract: Nasopharyngeal cancer is a type of malignant tumor with a high rate of incidence. Cancer stem cells are regarded as one of the main causes for the formation and recurrence of nasopharyngeal cancer. CXC chemokine receptor type 4 (CXCR4) has been reported to perform an important role in cancer; however, the association between CXCR4 and nasopharyngeal cancer stem cells remains unclear. The present study explored the effect of CXCR4 on cellular viability, apoptosis and invasion of nasopharyngeal cancer stem cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…However, a recent study showed that tamoxifen-resistant cells exhibit increased stemness properties via activation of Wnt/ß-catenin signaling (Leung et al, 2017). The interaction of CXC chemokine receptor type 4 (CXCR4) with its ligand CXC motif ligand 12 (CXCL12) plays important roles in maintaining CSCs properties in tamoxifen-resistant breast cancer cells (Dubrovska et al, 2012), nasopharyngeal CSCs (Tian et al, 2017), esophageal CSCs (Wang et al, 2017b), and stimulates the angiogenesis in vascular endothelial cells through upregulation of the MAPK/ERK and PI3K/AKT and Wnt/β-catenin pathways. (Song et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study showed that tamoxifen-resistant cells exhibit increased stemness properties via activation of Wnt/ß-catenin signaling (Leung et al, 2017). The interaction of CXC chemokine receptor type 4 (CXCR4) with its ligand CXC motif ligand 12 (CXCL12) plays important roles in maintaining CSCs properties in tamoxifen-resistant breast cancer cells (Dubrovska et al, 2012), nasopharyngeal CSCs (Tian et al, 2017), esophageal CSCs (Wang et al, 2017b), and stimulates the angiogenesis in vascular endothelial cells through upregulation of the MAPK/ERK and PI3K/AKT and Wnt/β-catenin pathways. (Song et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…When CSC is exposed to chemotherapeutic agents in vivo , some special regulatory mechanisms will be activated; pi3-K, MAPK and other pathways will be cascade-activated, and then the anti-apoptotic protein myeloid cell leukemia-1 (McL-1) will increase to inhibit the apoptosis of tumor cells ( 22 ). Many studies have suggested that inhibiting the activity of CSCs can increase the apoptosis of tumor cells ( 23 25 ). In another study by Zhang et al, CRCSCs were inhibited by pitavastatin, and the apoptosis of colon carcinoma cells was increased ( 26 ).…”
Section: Mechanisms Of Crcsc Chemotherapy Resistancementioning
confidence: 99%